If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1 + -1s) = -2(5s + 4) + 6s (1 * 7 + -1s * 7) = -2(5s + 4) + 6s (7 + -7s) = -2(5s + 4) + 6s Reorder the terms: 7 + -7s = -2(4 + 5s) + 6s 7 + -7s = (4 * -2 + 5s * -2) + 6s 7 + -7s = (-8 + -10s) + 6s Combine like terms: -10s + 6s = -4s 7 + -7s = -8 + -4s Solving 7 + -7s = -8 + -4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '4s' to each side of the equation. 7 + -7s + 4s = -8 + -4s + 4s Combine like terms: -7s + 4s = -3s 7 + -3s = -8 + -4s + 4s Combine like terms: -4s + 4s = 0 7 + -3s = -8 + 0 7 + -3s = -8 Add '-7' to each side of the equation. 7 + -7 + -3s = -8 + -7 Combine like terms: 7 + -7 = 0 0 + -3s = -8 + -7 -3s = -8 + -7 Combine like terms: -8 + -7 = -15 -3s = -15 Divide each side by '-3'. s = 5 Simplifying s = 5
| 3n+11=-16 | | 4y-9=18y+5 | | 2f-6=75+24 | | 10x+10=8x+2 | | 4(2-x)-3(7x+5)+6(3x-1)=2(8-x) | | 8x+9=5x+30 | | 3(x-2)-4(2x-3)=2(3x-1)-3(3x+1)+3 | | 3(2-3x)-2(5x-1)-3-2x=0 | | x-2(x-3)=5x+3(2x+2) | | 9x+24=5x+120 | | 5(3-x)-3(5-x)=0 | | -11=11(c-3) | | 99-5x=31x+15 | | 265-6x=39x+15 | | x^3+7x^2+200=0 | | 6(x-5)=-30 | | 15x=3(x-1)-4(1-x) | | -3=3(x+6) | | 149-5x=22x+23 | | 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 |